Metabolic Associations with Skin Tags - Azar Hadi Maluki; Aala Abidmuslim Abdullah (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2016)
Background: Skin tags are small, soft, pedunculated, often pigmented lesions, usually occurring on the eyelids, neck and axillae. There have been a few reports in the literature that the presence of skin tag is associated with different components of the metabolic syndrome. Objective: To evaluate the relationship between components of metabolic syndrome (atherogenic lipid, glucose level, hypertension, and waist circumference) and other metabolic associations with skin tags. Patients and Methods: A total of 51 patients with skin tags aged 16 to 64 years, 13 males (31.37%), 38 females (68.63%) with a mean age of (38.6 ± 12.1 SD); and 50 healthy controls aged 19 to 60 years, 13 males (30%) and 37 females (70%) with a mean age of (37.9 ± 9.4 SD) were examined in dermatology outpatient clinic of Kufa Medical School Teaching Hospital, Najaf, Iraq. Body Mass Index (BMI),waist circumference (WC),blood pressure (BP), fasting blood sugar (FBS), serum lipids including triglyceride, total cholesterol, high-density lipoprotein cholesterol (HDL), low-density lipoprotein cholesterol (LDL), liver enzymes (AST, ALT), alkaline phosphatase and serum uric acid were measured for both study groups. The study was approved by Ethics Committee of Kufa Medical School in Iraq. Results: There was no significant statistical difference in fasting blood sugar, serum uric acid, liver function tests, triglyceride, high density lipoprotein and very low density lipoprotein between the study groups. Patients group has showed significantly higher levels of total cholesterol and LDL, when compared with the healthy controls group (P < 0.01). Also patients group showed significantly higher values of BMI, blood pressure (BP), and Waist circumference (WC) compared with the healthy controls group (p = 0.0001), ( p = 0.001) and (P < 0.01) respectively. It has been found that 37 (72.5%) of the patients and 13 (26%) of the controls meet at least three of the criteria of metabolic syndrome. Conclusion: Total cholesterol and LDL serum levels should be checked in patients with skin tags. On the other hand, glucose, serum levels may not be as important as what is being considered in recent time.